Dark-humus soils on the updated soil map of Russian Federation scale 1 : 2.5 M - T. V. Ananko; M. I. Gerasimova (Бюллетень Почвенного института им. В.В. Докучаева, 2021)
The dark-humus soil type was included in the updated legend of the Soil Map of the Russian Federation at scale 1 : 2.5 M, converted to the system of Soil Classification of Russia. The soil profile starts with the dark-humus horizon gradually merging to the parent rock; any mid-profile diagnostic horizons are absent. Large areas of dark-humus soils are found in the forest-steppe, steppe and taiga zones of the European Russia, Western and Central Siberia, in the Trans-Baikal region, the Altai-Sayany Mountains, and the Caucasus. The type of dark-humus soils comprises both mesomorphic soils (of normal moisture conditions) and soils with additional surface or ground-water moisture. The main prerequisites for the formation of dark-humus soils are, on the one hand, the climatic conditions favorable for the dark-humus horizon formation, and, on the other hand, parent material - mostly derivates of hard rocks, restricting the development of mid-profile diagnostic horizons. In the updated map, the following initial legend units are partially or completely converted to dark-humus soils: several units of chernozems, dark-gray forest and gray forest non-podzolized soils, soddy-taiga base-saturated and slightly unsaturated soils, several mountain soils, a significant part of soddy-calcareous soils, as well as some mountainous forest-meadow soils. The diversity of dark-humus soils subtypes is determined by secondary carbonate features, weak signs of clay accumulation and podzolization, alteration of the mineral mass, gley and cryogenic phenomena.